Schools in rural areas and inclusive education – current condition and possibilities - Stamatović, Jelena; Maksimović, Jasna (Sociološki pregled, 2023)
The paper discusses the context of rural schools, and the current state and possibilities for the development of inclusive education in them. The law of the Republic of Serbia stipulates that all children must have access to and complete primary education, which implies, among other things, inclusive education, whereby each school must develop its own construct that matches the social and cultural circumstances in which the school operates, and the different needs of its students. The paper examines the presence of inclusive characteristics of education and the possibilities for improving inclusive education from the standpoint of teachers, on the sample of 160 teachers from 25 rural schools in Zlatibor district. A descriptive method and a survey method were applied. A special questionnaire for teachers, created for the purposes of this research, was used as the instrument. The results show that teachers estimate most of the characteristics of inclusive education as being present in their school, with the exception of inclusive teaching resources and assistive technologies. They see providing professional support and additional training for working with students who need support as the most important opportunity for improving the process of inclusive education.
Keywords: inclusive education; rural environment; rural schools; children who need additional support